Metallametallocenes: Sandwich Compounds of the First‐Row Transition Metals (M, M′ = Fe, Co, Ni) Containing a Metallacyclopentadiene Ring. Issue 12 (18th February 2013) - Zeng, Yi; Feng, Hao; Xie, Yaoming; King, R. Bruce; Schaefer, Henry F.
Abstract: Metallametallocenes are derived from metallocenes by replacing a CH unit in one of the cyclopentadienyl rings by a metal moiety. They include the known compounds CpCo(C4 H4 Co)Cp and CpFe(C4 Ph4 Ni)Cp (Cp = η 5 ‐C5 H5 ). The metallametallocenes of the type CpM(C4 H4 M′)Cp (M, M′ = Fe, Co, Ni) have been studied by density functional theory including the B3LYP* method of Reiher and collaborators to improve the reliability of predicted singlet‐triplet and double‐quartet splittings. The lowest‐energy structures for the homometallic metallametallocenes CpFe(C4 H4 Fe)Cp and CpCo(C4 H4 Co)Cp are triplet‐ and singlet‐spin‐state structures, respectively, that have formal metal–metal single bonds with predicted lengths of ca. 2.4 Å. The corresponding singlet CpFe(C4 H4 Fe)Cp structure with a much shorter Fe=Fe double bond length of ca. 2.27 Å is a significantly higher energy structure, which lies ca. 24 kcal/mol above the triplet structure. The lowest‐energy structure of the corresponding dinickel derivative CpNi(C4 H4 Ni)Cp is a triplet‐state structure that is suggested to have insignificant bonding between the nickel atoms. The lowest‐energy structures for the heterometallic derivatives CpM(C4 H4 M′)Cp (M ≠ M′ = Fe, Co, or Ni) are always the lowest‐spin‐state structure with the electron‐richest metal (Ni > Co > Fe) in the metallacyclic ring. The Wiberg bond indices that were determined by Natural Bond Orbital analysis appear to be the most reliable indication of formal metal–metal bond orders. Abstract : The lowest‐energy structures for CpM(C4 H4 M)Cp (M = Fe, Co, or Ni) are triplet‐, singlet‐, and triplet‐spin‐state structures, respectively, with formal metal–metal single bonds for the Fe and Co derivatives and no significant Ni··· Ni interaction for the Ni derivative. The lowest‐energy structures for the heterometallic derivatives CpM(C4 H4 M′)Cp (M, M′ = Fe, Co, or Ni) are always the lowest‐spin‐state structure with the electron‐richest metal atom in the metallacyclic ring.